Notes about two taxa belonging to Silene sect. Arenosae (Caryophyllaceae) - Jafari, Farzaneh; Rabeler, Richard K. (Phytotaxa, 2021)
Eggens et al. (2020) recently proposed to describe a new section Silene Linnaeus (1753: 416), i.e. sect. Arenosae Eggens, F.Jafari & Oxelman (in Eggens et al. 2020: 14), based on molecular and morphological data. A taxonomic treatment was provided including accepted names (with some nomenclatural changes), types, descriptions, distributions, and various notes. We have noticed two errors in that paper, the first one concerning the proposed new combination of S. kotschyi var. maritima Boissier (1867: 602), the second involving the typification of S. kowalenskyi Stschegleew (1853: 322). Corrections are presented below.